Epsilon-near-zero medium for optical switches in a monolithic waveguide chip at 1.9 μm - Jiang Xiantao; Lu Huiling; Li Qian; Zhou Hang; Zhang Shengdong; Zhang Han (Nanophotonics, 2018)
A saturable absorber is a building block for integrated ultrafast photonics and passive optical circuits. However, options currently available suffer from the bottlenecks of the necessity for fine control of the material preparation, large optical losses, and compatibility. This paper presents a complementary metal–oxide–semiconductor (CMOS)-compatible alternative based on an epsilon-near-zero (ENZ) medium, in which the real part of the dielectric constant vanishes. Excellent nonlinear optical modulations, including low linear optical losses, low bleaching threshold, moderate optical amplitude modulation, and high modulation speed of indium tin oxide (ITO) in its ENZ region are achieved. The use of ITO as an intracavity saturable absorber for optical switches of integrated waveguide chip lasers at 1.9 μm has been realized. A stable mode-locked waveguide laser with a repetition rate of 6.4 GHz and an average output power of 28.6 mW is achieved via carefully adjusting the intracavity three-surface interferometer (TSI). This work may pave the way for integrated photonics and electro-optics using a CMOS-compatible ENZ medium.